A hydrogel composite containing an interpenetrating network structure and a preparation method and application thereof
Patent Information
- Application Number
- CN202611287243.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-27
AI Technical Summary
此类超声耦合剂存在显著的应用局限性:其一,材料稳定性差、易流失液化,在超声探头持续移动、按压操作过程中极易损耗,需反复补涂,操作繁琐,难以适配人体浅表组织精准诊疗场景;其二,隔离防护效果不佳,探头、治疗头与人体皮肤直接频繁接触,易造成设备交叉污染,后续清洁维护工作量大;其三,生物应用安全性不足,传统液态耦合剂无法适配破损皮肤、给药创面等特殊场景,存在潜在安全风险,应用场景受到极大限制
1、本发明水凝胶复合物由温敏大分子构成的物理交联网络与水溶性聚合物构成的化学交联网络形成互穿结构,且体系中部分温敏大分子与水溶性聚合物形成共价连接,有效改善了水凝胶复合物的力学性能。
Smart Images

Figure CN122978628A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials technology, and more specifically to a hydrogel composite containing an interpenetrating network structure, its preparation method, and its application. Background Technology
[0002] Medical ultrasound coupling agents are used in ultrasound diagnostic and therapeutic procedures to fill or coat the space between the ultrasound probe, treatment head, and human tissue, eliminating air and preventing sound wave transmission from being affected or attenuated by air, thus enabling efficient transmission of ultrasound waves. With the rise of brain-computer interface technology, ultrasound coupling agents also play an indispensable role in the detection and stimulation of non-invasive ultrasound brain-computer interfaces.
[0003] Traditional ultrasound coupling agents are mostly water-soluble polymer gels, exhibiting a flowable state with weak mechanical properties, intended for application to human tissue. These agents have significant limitations: First, they suffer from poor material stability and are prone to liquefaction and loss during continuous movement and pressure of the ultrasound probe, requiring repeated reapplication, which is cumbersome and unsuitable for precise diagnosis and treatment of superficial tissues. Second, they offer poor isolation and protection, as the probe / treatment head frequently comes into direct contact with the skin, easily causing cross-contamination and requiring extensive subsequent cleaning and maintenance. Third, they lack sufficient biological safety; traditional liquid coupling agents cannot be used on broken skin or wounds, posing potential safety risks and severely limiting their application. Furthermore, traditional liquid coupling agents are functionally limited, only capable of basic ultrasound conduction, lacking thermal management, stable interface adhesion, and physiological electrical signal transmission capabilities, making them unsuitable for the multifunctional integrated diagnostic and treatment needs of current wearable monitoring, brain ultrasound therapy, and human motion sensing.
[0004] In recent years, solid-state ultrasound coupling patches have emerged, using natural or water-soluble synthetic polymers as substrates. These patches are cured to form a solid gel medium, significantly improving ease of use and effectively overcoming the drawbacks of traditional liquid coupling agents, such as easy flow, contamination, and limited applicability. However, existing commercially available and publicly reported solid-state ultrasound coupling patches still have several core performance shortcomings and poor overall compatibility: First, their mechanical robustness is insufficient. Most solid gel structures are brittle and have weak resistance to deformation, resulting in a mismatch with the mechanical properties of human skin. Under ultrasound pressure, local liquefaction and structural loosening are likely to occur, requiring greater pressure and easily causing discomfort to the patient's skin, posing a safety hazard. Second, their interfacial adhesion is lacking. Conventional solid patches have poor skin adhesion, and are prone to blistering and slippage under changes in body position or continuous pressure, severely interfering with ultrasound imaging. Clarity and treatment stability are important considerations. However, existing coupling gels generally lack thermal management capabilities. Under prolonged ultrasound irradiation and continuous operation of wearable devices, the heat generated by the device cannot be dissipated in time, easily causing skin irritation, redness, and damage. High temperatures also accelerate gel structure aging and deterioration, reducing the lifespan of the device and consumables. Finally, traditional solid-state coupling materials have limited functionality, only capable of transmitting ultrasound signals, unable to simultaneously handle bioelectrical signal transmission and human biomechanical sensing and monitoring. Their poor performance compatibility makes it difficult to achieve stable coupling and adaptation between rigid diagnostic and therapeutic equipment, flexible wearable devices, and human skin.
[0005] In summary, existing liquid and solid ultrasonic coupling media generally suffer from technical bottlenecks such as lack of thermal management, insufficient mechanical stability, poor skin adhesion, single signal transmission, and difficulty in achieving comprehensive performance. They cannot simultaneously meet the multifunctional requirements of stable storage and transportation, comfortable fit, efficient sound transmission, safe heat dissipation, multi-signal transmission, and long-term wear.
[0006] Therefore, developing an integrated thermosensitive solid-state ultrasound coupling patch that combines excellent thermal management and control capabilities, robust mechanical stability, skin-adaptive adhesion, efficient ultrasound and electrical signal transmission performance, and excellent biocompatibility is key to overcoming the shortcomings of existing technologies and expanding medical diagnosis and wearable sensing applications. It has significant clinical application value and market promotion prospects. Summary of the Invention
[0007] In view of this, the purpose of the present invention is to provide a hydrogel composite containing an interpenetrating network structure, its preparation method and application, so as to overcome the shortcomings of the prior art.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] A hydrogel composite containing an interpenetrating network structure comprises the following raw materials in parts by weight: 10-50 parts of a thermosensitive macromolecule and 10-50 parts of a water-soluble polymer.
[0010] The hydrogel composite of the present invention comprises a physical cross-linking network of a thermosensitive macromolecule with thermosensitive gel-sol phase transition properties and a chemical cross-linking network of a water-soluble polymer, wherein the physical cross-linking network and the chemical cross-linking network form an interpenetrating network, and there is also a partial covalent connection between the two networks.
[0011] In this invention, the temperature-sensitive macromolecules form a physical cross-linked structure, and the water-soluble polymer is formed by mixing the monomers with the temperature-sensitive macromolecules and then curing it at low temperature; during this process, 1% to 40% of the temperature-sensitive macromolecules form covalent bonds with the water-soluble polymers.
[0012] In this invention, the mechanical properties, bioadhesion, thermal management properties, and signal permeability of the hydrogel composite can be adjusted by regulating the ratio of temperature-sensitive macromolecules and water-soluble polymers.
[0013] Furthermore, the aforementioned temperature-sensitive macromolecule is gelatin, or a mixture of gelatin with carrageenan, sodium alginate, carboxymethyl chitosan, and hyaluronic acid.
[0014] Furthermore, the aforementioned water-soluble polymer is at least one of polyacrylamide and polyacrylic acid.
[0015] Furthermore, the aforementioned hydrogel composite containing an interpenetrating network structure further includes 10-50 parts of a water-soluble polyol. Even further, the water-soluble polyol is at least one selected from glycerol, ethylene glycol, and polyethylene glycol.
[0016] The further beneficial effect of the above-mentioned method is that water-soluble polyols can endow hydrogel complexes with excellent water retention and extended shelf life, enabling them to be stored for a long time.
[0017] Furthermore, the aforementioned hydrogel composite containing an interpenetrating network structure also includes 0.05 to 0.1 parts of a preservative. Even further, the preservative is one or more selected from sodium hydroxymethylglycinate, bis(hydroxymethyl)imidazolidinyl urea, imidazolidinyl urea, and potassium sorbate.
[0018] A method for preparing a hydrogel composite containing an interpenetrating network structure, specifically including the following steps: (1) Weigh each raw material according to the above-mentioned weight proportions of the hydrogel composite containing the interpenetrating network structure; (2) Add the thermosensitive macromolecule to the aqueous solution, stir to dissolve, and obtain a thermosensitive macromolecule solution; (3) Add the monomers, crosslinking agents and photoinitiators of the water-soluble polymer to the temperature-sensitive macromolecular solution, mix them evenly, and obtain a sol mixture; (4) The sol mixture is defoamed under vacuum and physically cured to obtain a pregel; (5) The pregel is cured by low temperature photocuring to obtain a hydrogel composite containing an interpenetrating network structure.
[0019] In this invention, the thermosensitive macromolecule (gelatin) and the water-soluble polymer (polyacrylamide) are thermodynamically incompatible. Directly mixing them at room temperature results in a sol mixture that undergoes phase separation, leading to poor pre-gel transparency and hindering photocuring and crosslinking. Therefore, by first uniformly dispersing the monomers of the water-soluble polymer, the crosslinking agent, and the photoinitiator within the thermosensitive macromolecule to form a sol mixture, and then controlling the pre-gel at low temperature to freeze the chain movement of the thermosensitive macromolecule, the phase separation of the water-soluble polymer and the thermosensitive macromolecule during polymerization and crosslinking is avoided kinetically. This is of great significance in controlling the chemical structure of the hydrogel composite. Therefore, this invention employs a low-temperature photocuring method, which can effectively regulate the chemical structure of the hydrogel composite, resulting in a homogeneous structure with a unique structure where the thermosensitive macromolecule and the water-soluble polymer are covalently linked in a certain proportion. This structure not only satisfies the thermal management and bioadhesion properties of the hydrogel composite but also imparts superior mechanical and signal transmission performance.
[0020] Furthermore, in step (2) above, the aqueous solution is deionized water, and the temperature is 40~90 °C, preferably 70 °C; the ratio of the amount of temperature-sensitive macromolecule to the amount of aqueous solution is 1:(6~8).
[0021] Further, in step (3) above, the monomer of the water-soluble polymer is at least one of acrylamide and acrylic acid; the crosslinking agent is at least one of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, pentaerythritol triacrylate and trimethylolpropane triacrylate; the photoinitiator is at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate and 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenylacetone; the ratio of the thermosensitive macromolecule, the monomer of the water-soluble polymer, the crosslinking agent and the photoinitiator is (5~20):(5~20):(0.025~0.2):(0.01~0.04), preferably 10:10:0.05:0.02; the mixing temperature is 40~90 °C, preferably 70 °C.
[0022] The further beneficial effect of the above-mentioned method is that the monomers and crosslinking agents of the water-soluble polymer polymer are polymerized under the action of the photoinitiator to form a chemical crosslinking network.
[0023] Furthermore, in step (4) above, the temperature of vacuum defoaming is 40~90 °C, preferably 70 °C, and the time is 10~30 min, preferably 20 min; the temperature of physical curing is -20~0 °C, preferably -10 °C, and the time is 10~20 min, preferably 15 min.
[0024] The further beneficial effect of the above-mentioned method is that, through vacuum defoaming, the micro-bubbles trapped in the sol system are fully removed, ensuring that the subsequent gel has a uniform texture and consistent light transmittance. Through low-temperature physical curing, the sol system is initially formed, resulting in a pregel blank with a complete structure, regular shape, and no shrinkage or deformation.
[0025] Furthermore, in step (5) above, the temperature for low-temperature photocuring is -20~0 °C, preferably -10 °C, and the time is 10~60 min, preferably 30 min.
[0026] The further beneficial effect of adopting the above is that, through low-temperature photocuring, the photocuring crosslinking reaction within the system is triggered, allowing the monomers of the water-soluble polymer to fully polymerize and crosslink, thus constructing a dense and stable interpenetrating composite structure with the temperature-sensitive macromolecular network.
[0027] This invention also claims the use of the above-mentioned hydrogel composite containing an interpenetrating network structure in the preparation of ultrasonic coupling patches. The specific application is as follows: (1) To work with the detection probe to complete the imaging of human or animal tissues; (2) It adheres to the scalp where hair has been removed and works in conjunction with the treatment head to provide ultrasonic stimulation and treatment to the human brain tissue; (3) Adhere to human skin, connect to a resistance detector, and form a human motion sensor.
[0028] The hydrogel composite of this invention can be manufactured into ultrasound coupling patches of different shapes and specifications simply by adjusting the mold dimensions according to usage requirements. The shapes are conventional sizes and shapes used in diagnostic or therapeutic devices, including but not limited to circular and irregular shapes. Specifically, the diameter × thickness of the circular patch is 80×8 mm, 80×10 mm, 80×15 mm, 80×20 mm, 90×10 mm, 90×15 mm, 90×20 mm, 90×25 mm, 15×2 mm, 20×2 mm, and 25×5 mm. The thickness of the irregular shape is 2 mm, 10 mm, 20 mm, and 25 mm. The shape and size of the solid medical ultrasound coupling patch prepared from the hydrogel composite of this invention are not limited to the above. The shape and size can be defined according to the medical needs and the site of ultrasound examination or treatment. A thickness of 20 mm or more is generally used for superficial ultrasound examinations or treatments.
[0029] As can be seen from the above technical solution, compared with the prior art, the beneficial effects of the present invention are as follows: 1. The hydrogel composite of the present invention forms an interpenetrating structure by a physical cross-linking network composed of temperature-sensitive macromolecules and a chemical cross-linking network composed of water-soluble polymers. Furthermore, some temperature-sensitive macromolecules in the system form covalent bonds with the water-soluble polymers, which effectively improves the mechanical properties of the hydrogel composite.
[0030] 2. The present invention adopts a low-temperature photocuring preparation process, which can effectively construct covalent links between temperature-sensitive macromolecules and water-soluble polymers, ensuring that the hydrogel is transparent, uniform, and structurally stable.
[0031] 3. The hydrogel complex of the present invention has mechanical properties that are compatible with human skin, excellent acoustic properties, tissue adhesion and good biocompatibility. At the same time, the thermosensitive macromolecules endow the hydrogel complex with phase change heat management properties, which can prevent the high temperature generated during the operation of electronic devices from damaging the skin.
[0032] 4. The hydrogel composite of the present invention can be prepared as an ultrasound coupling patch, which can be applied to ultrasound imaging of superficial human tissues, scalp-adhesive brain ultrasound stimulation and treatment, and can also be attached to human skin to construct human motion sensors. It can be applied to medical ultrasound diagnosis and treatment, non-invasive brain-computer interface and human motion monitoring fields, with a wide range of applications and strong clinical applicability. Attached Figure Description
[0033] Figure 1 The diagram shows the structure of the hydrogel composite of Example 1 (A) and the X-ray photoelectron spectroscopy results of each sample (B); Note: The assignments of each peak are marked in the figure. The arrows in Example 1 and Example 1 (after extraction) point to the unique chemical bonds CO (286.5 eV) and OC=O (288.8 eV) of the physical cross-linking component gelatin. Figure 2 Statistical bar charts of stress, elongation at break, tensile strength, and Young's modulus for each sample; Figure 3 The 90° peel curves and corresponding peel energy histograms of the hydrogel composite and commercial cardiac electrode patch in Example 1 are shown. Figure 4 Bar graph showing the surface temperature rise of each sample on the hot plate; Note: The black line represents 37 °C. Figure 5 The image shows a bar graph of the sound velocity at 25 °C for the hydrogel complex, air, water, and skin in Example 1. Detailed Implementation
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] Example 1 A hydrogel complex containing an interpenetrating network structure comprises the following raw materials by weight: 8 g gelatin (powder), 0.5 g carrageenan, 0.5 g sodium alginate, 0.5 g carboxymethyl chitosan, 0.5 g hyaluronic acid, 10 g polyacrylamide, 5 g glycerol, 5 g ethylene glycol, 0.05 g potassium sorbate (medical grade), and 69.95 g deionized water; Polyacrylamide is prepared by photocuring reaction of acrylamide, N,N'-methylenebisacrylamide and lithium phenyl (2,4,6-trimethylbenzoyl)phosphate. The preparation method of the above-mentioned hydrogel composite containing an interpenetrating network structure specifically includes the following steps: (1) Weigh each raw material Weigh each raw material according to the mass of the hydrogel composite containing the interpenetrating network structure described above. (2) Preparation of thermosensitive macromolecular solutions A mixture of 8 g gelatin, 0.5 g carrageenan, 0.5 g sodium alginate, 0.5 g carboxymethyl chitosan and 0.5 g hyaluronic acid was dispersed in 69.95 g of sterile deionized water heated at 70 °C. The mixture was kept at this temperature and stirred until the gelatin was completely swollen and dissolved. The system was homogeneous and transparent, with no solid particles or flocculent precipitates, thus obtaining a temperature-sensitive macromolecular solution. The entire process was carried out in a sealed, dust-proof manner to avoid contamination by impurities. (3) Preparation of sol mixture 10 g acrylamide, 0.05 g N,N'-methylenebisacrylamide, 0.02 g lithium phenyl (2,4,6-trimethylbenzoyl) phosphate, 5 g glycerol, 5 g ethylene glycol and 0.05 g potassium sorbate were added sequentially to a thermosensitive macromolecular solution and stirred continuously at a constant temperature of 70 °C until all components were completely mixed to form a homogeneous, transparent, stable sol mixture without layering and no visible bubbles. (4) Vacuum defoaming and physical curing The sol mixture was transferred to a vacuum defoaming device and kept at a constant temperature of 70 °C and negative pressure vacuum for 20 minutes to defoam. After defoaming, it was sealed and stored in time to avoid secondary air intake and mixing of air bubbles. Then, the homogeneous sol mixture after defoaming was smoothly injected into the medical custom silicone mold and the mold was placed in a low temperature environment of -10 °C for 15 minutes to obtain pre-gel. (5) Low-temperature photocuring and post-treatment Under a low temperature of -10°C, the pregel was subjected to overall photocuring treatment with a specific wavelength light source for 30 min. After photocuring, it was naturally demolded, and excess waste at the edges was trimmed and removed. After encapsulation, a hydrogel composite with an interpenetrating network structure with stable performance and excellent transparency was finally obtained.
[0036] Example 2 The hydrogel composite containing an interpenetrating network structure differs from Example 1 only in that the heat preservation temperature of physical curing in step (4) and low-temperature photocuring in step (5) is adjusted to 0 °C, while the other steps remain unchanged, thus preparing a hydrogel composite containing an interpenetrating network structure with low covalent linkage of temperature-sensitive macromolecules.
[0037] Performance testing 1. Regulation of covalent bonding between thermosensitive macromolecular physical crosslinking components and water-soluble polymers in hydrogel complexes The hydrogel composites of Examples 1 and 2 were extracted with water at 37 °C for 24 h to completely remove the physically cross-linked structural components, yielding the extracted hydrogel composites of Examples 1 and 2, respectively. The hydrogel composite of Example 1, the extracted hydrogel composite of Example 1, gelatin, and polyacrylamide were freeze-dried together and then subjected to X-ray photoelectron spectroscopy analysis. The results are as follows: Figure 1 As shown.
[0038] Depend on Figure 1 It can be seen that the XPS C 1s peak of the hydrogel complex of Example 1 after extraction still retains the unique chemical bonds CO (286.5 eV) and OC=O (288.8 eV) of the physically cross-linked gelatin, proving that some gelatin is covalently linked to the chemical cross-linked structure of polyacrylamide.
[0039] The hydrogel composites of Example 1, the extracted hydrogel composites of Example 1, and the extracted hydrogel composites of Example 2 were freeze-dried and weighed for comparison. The results showed that 40% of the original gelatin in the extracted hydrogel composite of Example 1 could not be removed and existed as a covalent link in the extracted hydrogel composite; similarly, 1% of the original gelatin in the extracted hydrogel composite of Example 2 could not be removed and existed as a covalent link in the extracted hydrogel composite.
[0040] 2. Mechanical testing results of the hydrogel composite According to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", tensile mechanical properties tests were carried out on the hydrogel composites of Examples 1-2, gelatin and polyacrylamide respectively to evaluate the mechanical properties of the hydrogel composites.
[0041] (1) Sample preparation The hydrogel composites of Examples 1-2, gelatin, and polyacrylamide were respectively cut into standard dumbbell-shaped tensile specimens. The effective tensile section dimensions of the specimens were: width 4 mm, thickness 4 mm, and gauge length 20 mm.
[0042] (2) Test equipment and test conditions The universal testing machine was used with a tensile rate set to 20 mm / min and an ambient temperature of 25 °C. The stress-strain curve of the specimen was obtained, and the stress, elongation at break, tensile strength, and Young's modulus of the specimen were tested.
[0043] (3) Test results Depend on Figure 2 It can be seen that the hydrogel composite of Example 1 has a tensile strength of 0.21 MPa, an elongation at break of 480%, and an elastic modulus of 0.046 MPa. Meanwhile, the elastic modulus of human epidermal skin typically ranges from 0.04 to 0.08 MPa. The comparison shows that the elastic modulus of the hydrogel composite of Example 1 falls within the mechanical range of human skin, demonstrating excellent mechanical compatibility.
[0044] (4) Results Analysis Depend on Figure 2 It is known that when acrylamide is cured at low temperature to form cross-linked polyacrylamide, and then forms an interpenetrating network with gelatin, the tensile strength and elongation at break of the gel are significantly improved, while the elastic modulus is reduced to a level close to that of human skin.
[0045] During ultrasound diagnostic procedures, the hydrogel composite of this invention can stretch synchronously with the skin's deformation, making it less prone to cracking or breaking; at the same time, it can achieve a close fit without applying large pressure, reducing the patient's discomfort from pressure.
[0046] In addition, the hydrogel composite of the present invention contains thermosensitive macromolecules such as gelatin, which soften at body temperature, further reducing the apparent modulus. This allows it to be adapted to irregular areas such as joints, scalp, and curved surfaces of the body. When pressure is applied with an ultrasound probe or treatment head, the interface fits well, effectively venting air gaps and ensuring stable ultrasound transmission. At the same time, it can solve the defects of existing solid ultrasound coupling patches, such as easy liquefaction, excessive hardness, and poor comfort.
[0047] 3. Adhesion experiment of hydrogel complex on pigskin To verify the adhesion ability, interface stability and adhesion reliability of the hydrogel composite of the present invention to the biological skin interface, an ex vivo pig skin was used as a biomimetic skin model to carry out a 90° peel mechanical adhesion test to simulate the patch adhesion performance under human skin application, ultrasonic pressure and dynamic body position change scenarios.
[0048] (1) Sample preparation and biomimetic substrate treatment Fresh, undamaged, and grease-free detached pigskin was selected as the test substrate. Excess subcutaneous fat was removed, and the skin was cleaned, disinfected, and left to stand at room temperature for later use. The hydrogel composite from Example 1 was cut into test strips of uniform specifications, and a commercial cardiac electrode patch was used as a comparison. Before testing, the patch was attached to the surface of the pigskin and placed at a constant temperature simulating human body temperature for a period of time to allow the gel to fully soften and the interface to be fully wetted and adhered.
[0049] (2) Test method A 90° peel test was conducted using a universal material mechanical testing machine. The experiment was carried out according to the conventional method for testing medical adhesive hydrogels. An appropriate peel rate was set, the peel angle was kept constant at 90°, and the sample was peeled continuously and uniformly. The peel curve was recorded throughout the peeling process.
[0050] (3) Test Results and Analysis Depend on Figure 3 It can be seen that the hydrogel composite of Example 1 adheres tightly to the interface of pigskin, the interface is uniform during the peeling process, there is no instantaneous detachment or local hollowing and falling off, the peeling force value is stable, and the interface adhesion performance is moderate.
[0051] Compared to commercial cardiac electrode patches, the interpenetrating covalent composite network structure of this invention significantly improves the toughness and interfacial wettability of the gel surface. The thermosensitive softening properties allow the gel to adapt to the micro-texture of the skin and adhere tightly. At the same time, the adhesion force is moderate, which can meet the requirements of long-term adhesion without displacement or falling off during ultrasound detection and brain treatment, and can also achieve non-invasive and easy peeling without sticking to the skin, tearing the skin, or leaving any residue.
[0052] 4. Thermal management evaluation of hydrogel complexes Examples 1 hydrogel composites, gelatin, polyacrylamide, and a commercially available ultrasonic coupling patch of equal thickness (2 mm) and size (1 cm × 1 cm) were placed simultaneously on a hot plate and heated uniformly from room temperature. The surface temperatures at the start of heating were characterized at 0 min, 5 min, 10 min, and 15 min.
[0053] Depend on Figure 4 It is known that gelatin melts shortly after heating because the temperature of the hot plate is higher than its gel-sol transition temperature, and its surface temperature is consistent with that of the hot plate (50 °C). The hydrogel composite in Example 1 maintained a temperature below body temperature (37 °C), demonstrating its excellent thermal management capabilities, which effectively dissipate the heat of the device when it is applied to the skin via the gel, thus protecting the skin.
[0054] 5. Acoustic performance test results of the hydrogel composite According to the industry standard YY / T 0299-2022 "Medical Ultrasonic Coupling Agent", the core acoustic performance indicators of the hydrogel composite in Example 1 were tested. The testing temperature was set at 35°C (the normal testing temperature for the human body). The specific test items and results are as follows: (1) Sound velocity detection: Detected using an ultrasonic sound velocity tester, by... Figure 5 It can be seen that the sound velocity of the hydrogel composite in Example 1 is 1576 m / s, which is within the optimal range of 1520~1620 m / s in the industry standard. It is highly matched with the sound velocity of human soft tissue and can minimize the sound wave interface reflection loss. (2) Acoustic impedance test: The acoustic impedance of the hydrogel composite of Example 1 was measured to be 1.68 × 10⁻⁶. 6 Pa·s / m, conforming to industry standard 1.5×10 6 ~1.7×10 6 The Pa·s / m requirement is met, and the impedance matching with human skin and muscle tissue is excellent, enabling efficient transmission of ultrasound.
[0055] (3) Sound attenuation coefficient detection: The sound attenuation coefficient of the hydrogel composite in Example 1 was 0.034 dB / (cm·MHz), which is far below the industry standard limit of ≤0.1 dB / (cm·MHz). The sound wave penetration loss is extremely low and the ultrasonic imaging clarity is high.
[0056] 6. NIH-3T3 cytotoxicity assay of the hydrogel complex According to GB / T 16886.5-2017 / ISO 10993-5:2009 Standard for In Vitro Cytotoxicity Testing of Medical Devices, NIH-3T3 mouse fibroblasts were used to detect the cytotoxicity of the hydrogel complex in Example 1 using the extraction method to assess the product's biocompatibility. The specific experimental procedure and results are as follows: (1) Experimental materials and grouping: The experimental cells were NIH-3T3 mouse fibroblasts. The culture medium used was DMEM high glucose medium containing 10% fetal bovine serum. A blank control group (cells cultured in pure culture medium), an experimental group (cells cultured in the hydrogel complex extract of Example 1), and a negative control group (medical sterile silicone patch extract) were set up.
[0057] (2) Preparation of sample extract: The sterilized hydrogel complex of Example 1 was added to sterile DMEM medium at an extraction ratio of 0.1 g / mL and extracted at 37 °C and 5% CO2 for 24 h. The supernatant was collected as the extract of the hydrogel complex of Example 1 and filtered aseptically for later use.
[0058] (3) Cell culture and detection: NIH-3T3 cells were cultured at 5×10⁻⁶ cells / year. 3Cells were seeded at a density of [number] cells / well in 96-well cell culture plates, with the corresponding culture medium added to each well. Six replicates were set up for each group. Cells were incubated continuously at 37 °C, 5% CO2, and saturated humidity for 12 h. After seeding, the extract medium from each group was replaced, and cells were cultured for another 24 h. After the end of the culture period, 20 μL of CCK8 solution was added to each well, and the cells were incubated for 30 min. The absorbance at 450 nm was measured using a microplate reader, and cell viability and cytotoxicity levels were calculated.
[0059] (4) Experimental results: The NIH-3T3 cells in the experimental group were morphologically intact, adhered well, and proliferated normally, without shrinkage, rupture, apoptosis, or shedding. The cell survival rate in the experimental group was 97.7%, while the cell survival rate in the negative control group was 96.3%, with no significant difference between the two groups. According to the standard cytotoxicity grading, the cytotoxicity of the hydrogel complex in Example 1 was grade 0 (no cytotoxicity), which is far superior to the safety requirement of ≤2 grade for medical devices. It has excellent biocompatibility and no potential risk of cell damage.
[0060] 7. Hydrogel complexes are used for imaging superficial human tissues. (1) Selection of patch specifications The hydrogel composite from Example 1 was used to prepare a circular ultrathin product with a diameter of 25 mm and a thickness of 1-2 mm by adjusting the thickness.
[0061] (2) How to use The hydrogel composite of Example 1 is directly applied to the superficial tissue detection site (subcutaneous blood vessels, epidermal soft tissue, superficial lymph nodes, thyroid surface, etc.) and pressed to ensure complete adhesion between the hydrogel composite of Example 1 and the skin, eliminating interfacial air. The medical ultrasound detection probe is then tightly attached to the surface of the hydrogel composite of Example 1, and the ultrasound equipment is activated to perform superficial tissue imaging detection.
[0062] (3) Usage effect and performance verification Example 1: The hydrogel composite exhibits a thin profile and excellent flexibility, softening rapidly at body temperature to adhere closely to uneven superficial skin; its acoustic properties are stable, with a sound attenuation coefficient maintained between 0.030 and 0.040 dB / (cm²). (MHz), with no additional acoustic loss. The image is clear with high boundary resolution and no artifacts or clutter interference.
[0063] Compared to traditional liquid coupling agents, the hydrogel composite of Example 1 does not have the problems of dripping or spilling, and the entire detection can be completed with a single application without the need for repeated reapplication. Compared to conventional thick solid coupling patches, the ultra-thin structure of the hydrogel composite of Example 1 is more suitable for the high-precision imaging requirements of superficial tissues, with low pressure resistance and no obvious discomfort to the subjects, making it suitable for outpatient batch superficial ultrasound screening.
[0064] 8. Application of hydrogel complexes in ultrasound stimulation and treatment of human brain tissue (1) Selection of patch specifications Take the hydrogel composite from Example 1, adjust the thickness to obtain a circular coupling patch of conventional thickness with a diameter of 90 mm and a thickness of 10 mm, and use it after medical sterilization.
[0065] (2) How to use Select the target area of the subject's scalp, thoroughly remove hair, and clean and disinfect to ensure the scalp surface is dry, free of oil, and undamaged. Adhere the hydrogel composite of Example 1 completely to the target area of the scalp after hair removal, and gently press to ensure a tight and comprehensive fit between the hydrogel composite and the scalp. Align the ultrasonic treatment head with the center of the hydrogel composite of Example 1 and attach it firmly. After fixing the treatment head in position, activate the ultrasound equipment according to the clinical protocol to perform targeted ultrasound stimulation and treatment on the human brain tissue.
[0066] (3) Verification of usage effectiveness and safety Example 1: The hydrogel composite exhibits thermosensitive properties, softens sufficiently at human scalp temperature, adheres well, and can conform to the curved contours of the head without shifting or falling off throughout the process; the interpenetrating network structure formed by gelatin and cross-linked polyacrylamide has mild mechanical properties, and does not cause pressure even after prolonged application.
[0067] The acoustic impedance is matched step-by-step with the human scalp, skull, and brain tissue, allowing ultrasound waves to efficiently penetrate the scalp and skull to act on the target brain tissue. The sound conduction is stable and the treatment energy loss is low.
[0068] After 2 hours of continuous clinical simulation, the test subjects' scalps showed no irritation such as erythema, edema, or itching. Combined with in vitro testing, the hydrogel complex of Example 1 remained stable in terms of structure, acoustic properties, and monomer residual rate after long-term exposure to therapeutic-grade ultrasound.
[0069] Meanwhile, the hydrogel composite of Example 1 can form a physical barrier between the probe and the scalp, effectively avoiding cross-contamination caused by direct contact between the treatment head and the scalp. It is easy to clean and fully meets the clinical safety requirements for brain ultrasound stimulation, neurorehabilitation, and targeted brain ultrasound therapy.
[0070] The above experiments demonstrate that this invention, through optimizing the gelatin-crosslinked polyacrylamide interpenetrating network temperature-sensitive system and combining it with a low-temperature blue light curing process, prepares a hydrogel composite with extremely low monomer residue and excellent acoustic transmission performance. It also exhibits high biocompatibility (grade 0 cytotoxicity, no skin irritation), and its mechanical properties are highly compatible with human skin. It can adaptively conform to the skin at body temperature without requiring significant pressure. This completely solves the technical defects of traditional liquid coupling agents, such as easy loss and high risk of contamination, and existing solid coupling agents, such as easy liquefaction, mechanical mismatch, and unstable sound transmission. It can be widely applied to various ultrasound diagnostic and treatment scenarios, with broad application scope and strong clinical applicability.
[0071] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A hydrogel composite containing an interpenetrating network structure, characterized in that, The raw materials include the following parts by weight: 10-50 parts of thermosensitive macromolecules and 10-50 parts of water-soluble polymers.
2. The hydrogel composite containing an interpenetrating network structure according to claim 1, characterized in that, The temperature-sensitive macromolecule is gelatin, or a mixture of gelatin with carrageenan, sodium alginate, carboxymethyl chitosan, and hyaluronic acid.
3. The hydrogel composite containing an interpenetrating network structure according to claim 1, characterized in that, The water-soluble polymer is at least one of polyacrylamide and polyacrylic acid.
4. The hydrogel composite containing an interpenetrating network structure according to claim 1, characterized in that, It also includes 10-50 parts of water-soluble polyols.
5. The hydrogel composite containing an interpenetrating network structure according to claim 4, characterized in that, The water-soluble polyol is at least one of glycerol, ethylene glycol, and polyethylene glycol.
6. The hydrogel composite containing an interpenetrating network structure according to claim 1, characterized in that, It also includes 0.05 to 0.1 parts of preservative.
7. The hydrogel composite containing an interpenetrating network structure according to claim 6, characterized in that, The preservative is one or more of sodium hydroxymethylglycinate, bis(hydroxymethyl)imidazolidinyl urea, imidazolidinyl urea, and potassium sorbate.
8. A method for preparing a hydrogel composite containing an interpenetrating network structure, characterized in that, Specifically, the following steps are included: (1) Weigh each raw material according to the weight proportions of the hydrogel composite containing the interpenetrating network structure as described in any one of claims 1 to 7; (2) Add the thermosensitive macromolecule to the aqueous solution, stir to dissolve, and obtain a thermosensitive macromolecule solution; (3) Add the monomers, crosslinking agents and photoinitiators of the water-soluble polymer to the temperature-sensitive macromolecular solution, mix them evenly, and obtain a sol mixture; (4) The sol mixture is defoamed under vacuum and physically cured to obtain a pregel; (5) The pregel is cured by low temperature photocuring to obtain the hydrogel composite containing the interpenetrating network structure.
9. The method for preparing a hydrogel composite containing an interpenetrating network structure according to claim 8, characterized in that, In step (2), the aqueous solution is deionized water at a temperature of 40-90 °C; the ratio of the thermosensitive macromolecule to the aqueous solution is 1:(6-8). In step (3), the monomer of the water-soluble polymer is at least one of acrylamide and acrylic acid; the crosslinking agent is at least one of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, pentaerythritol triacrylate, and trimethylolpropane triacrylate; the photoinitiator is at least one of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate and 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenylacetone; the ratio of the thermosensitive macromolecule, the monomer of the water-soluble polymer, the crosslinking agent, and the photoinitiator is (5~20):(5~20):(0.025~0.2):(0.01~0.04); the mixing temperature is 40~90 °C; In step (4), the temperature of vacuum defoaming is 40~90 °C and the time is 10~30 min; the temperature of physical curing is -20~0 °C and the time is 10~20 min. In step (5), the temperature for low-temperature photocuring is -20~0 °C and the time is 30 min.
10. The use of a hydrogel composite containing an interpenetrating network structure as described in any one of claims 1 to 7 in the preparation of an ultrasonic coupling patch.